KEBIJAKSANAAN KHALIFAH UTSMAN IBN AFFAN YANG KONTRAVERSIALDALAM PEMERINTAHANNYA - Syamruddin Nasution (An-Nida', 2015)
The present article dealswith three main problems, namely, ‘Utsmân in his capacity as the third among the four true guided caliphs (al-khulafâ’ al-râsyidûn), the rivalry between Hasyimite and Umayyah clans, and the contro-versial policies as well as favoritism in his regime. Each problem has different focuses. With regard to the first, an attempty will be given to analyze whether this companion and son-in-law of the prophet Muhammad was a professional and trust worthy caliph or not; the second will evaluate the history and nature of their rivalry; and the third will concentrate on his four controversy policies, i.e., political nepotism, the mutation of the head of Bayt al-Mâl, distributing the state treasury to his relatives, and the practices of purchase-and-sale the land of the Muslim state. Using the method of descriptive analysis on ‘Utsmân and his related historical events as a caliph, this study finds that the era of ‘Utsmân marked the rise of Umayyah clan to power. He was also a trusted yet unprofessional leader, as seen from his incapability insupervising and controlling the maneuver of his secretary, Marwân bin $akam, i.e., his cousin and son-in-law, who was responsible behind the practice of nepotism in ‘Utsmân’s regime and issuing controver-sial policies, which eventually led to the riot at the cost of ‘Utsmân’s life.